THE CITY AND LANDSCAPE OF UR: AN AERIAL, SATELLITE, AND GROUND REASSESSMENT. (December 2019) - Hammer, Emily
Abstract : New fieldwork at Ur has begun to investigate urban scale, city organization, and the environment of the city's hinterland. Analysis of new sources of declassified aerial and satellite imagery from the 1950s and 1960s, recent unmanned aerial vehicle (UAV) photos, and a systematic surface collection show that Ur may have expanded to between 120–500 hectares in size during its later periods of habitation, far larger than the sixty hectare maximum size previously estimated. Traces of buried architecture visible in the UAV photos and topographic models generated from UAV photos allow for the generation of hypotheses about the city plan of Ur during the Late Larsa/Old Babylonian and Neo Babylonian periods. Relict watercourses mapped in the vicinity of the main mound indicate how the city might have been supplied with water in some periods. Alongside this site-based work, historical aerial and satellite imagery provide an updated picture of ancient hydrology, environment, and settlement patterns around Ur.